PINJAMAN KORPORASI: BANK KOMERSIAL DAN BANK INVESTASI - Sari Gondokusumo; Liliana Inggrit Wijaya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
The increasing of fund had followed the investment bank growth between 1990-1997. Different type of institution also has different loan pricing between commercial bank and investment bank. Basically their differences depend on several factors like these: sources of fund, government rules, borrower’s relationship, market share, and accounting principles. The aims of this research purpose are testing the differences loan pricing between commercial bank and investment bank before crises period. Variables use in this research is types of bank institution, loan duration, loan amount, collateral, and listing Borrowers Company. Controlling variables are industry and term of loan contract. The testing is also for the level of asymmetry information by listed and non-listed borrowers, versus foreign and domestic lenders. For statistic inferential test is using by Ordinary Least Squares regression with white correction heteroscedasticity. Data collection comes from Dealscan database support by LPC (Loan Pricing Corporation). Meanwhile, the data sampling are before crises start from 1990 until 1997. Finally this research result has proven there are any differences between commercial bank and investment bank borrowing. Therefore, commercial bank more focus on lender come from and investment bank more serious attention to borrower’s types. The commercial bank get better than investment bank, even both of them still only look at the general factors, for instance; maturity, collateral, and borrowing types .